2020
DOI: 10.1039/d0fo00537a
|View full text |Cite
|
Sign up to set email alerts
|

The effects of betalain-rich cacti (dragon fruit and cactus pear) on endothelial and vascular function: a systematic review of animal and human studies

Abstract: This systematic review assesses the evidence for the effects of edible cacti (dragon fruit and cactus pear) on vascular and endothelial function based on animal models and human studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 48 publications
0
10
0
1
Order By: Relevance
“…Blood glucose levels reflect the amount of glucose released into the blood stream following food consumption, which is an important parameter to measure, since high blood glucose levels can cause diabetes, high blood pressure and other chronic diseases [68]. Red pitaya is a potential medicinal plant for attenuation of blood glucose due to the regeneration of pancreatic β-cells that synthesise and secrete insulin and amylin (two hormones that regulate blood glucose levels) [4].…”
Section: Glycaemic Controlmentioning
confidence: 99%
“…Blood glucose levels reflect the amount of glucose released into the blood stream following food consumption, which is an important parameter to measure, since high blood glucose levels can cause diabetes, high blood pressure and other chronic diseases [68]. Red pitaya is a potential medicinal plant for attenuation of blood glucose due to the regeneration of pancreatic β-cells that synthesise and secrete insulin and amylin (two hormones that regulate blood glucose levels) [4].…”
Section: Glycaemic Controlmentioning
confidence: 99%
“…In recent years, there has been increased clinical need for, and strong research efforts focused on, natural approaches to MetS management [78,79] and even food supplementation with OFI [80][81][82][83]. Although our study was relatively small and limited in drawing any definitive inferences, especially in view of inter-/intra-individual variability, the preliminary data presented herein is highly suggestive of a potential beneficial protective activity of OFI extract on CVD based on its effects on both lipid and glucose metabolism.…”
Section: Discussionmentioning
confidence: 79%
“…Other health benefits include balancing of the production of blood by enhancing the levels of erythrocyte and haemoglobin, the formation of cardiac tissues, prevention of cancer in the colon and prostate and minimizing aortic stiffness (Kumar et al, 2018). These betalain rich fruits are also reported to enhance the functions of the endothelium and vascular system (Cheok et al, 2020).…”
Section: Pharmacognosy and Medicinal Propertiesmentioning
confidence: 99%
“…According to the studies conducted by Cheok et al (2020), one of the major bioactive compounds found in Dragon fruits are the betalains. Around 85 per cent of their total phenolics are composed of betalainic compounds (Esquivel et al, 2007).…”
Section: Pharmacognosy and Medicinal Propertiesmentioning
confidence: 99%